PRODUCTION OF PROTEIN CONCENTRATE EXTRACTED FROM BLACK SEA CUCUMBER (Holothuria edulis) BY USING DIFFERENT EXTRACTION SOLVENTS - Afriadi Sinaga; Mery Sukmiwati; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was objected to determine the effect of different extraction solvents on the quality of black sea cucumber (Holothuria edulis) protein concentrate. The characteristic and quality of the black sea cucumber protein concentrate produced were determined by assessing the rendemen, proximate composition, and total amino acid. This research was conducted in two phases, namely: 1) production of black sea cucumber powder, and 2) production of black protein concentrate by using different extraction solvents, namely: ethanol, acetone, and chloroform. The result showed that the using of different extraction solvents was significantly affected on the characteristic of black sea cucumber protein concentrate. Ethanol was indicated the best solvent to extract the black sea cucumber to yield 80,42% protein concentrate. The product was contained total ash 25.03%, moisture 5.4%,  protein 61.32%,  fat 0.5%, and the total amino acid 14.14%. Keywords : protein concentrate, extraction, extractor solution, sea cucumber.